Glycosyltransferase OsUGT90A1 helps protect the plasma membrane during chilling stress in rice. (24th January 2020) - Shi, Yao; Phan, Huy; Liu, Yaju; Cao, Shouyun; Zhang, Zhihua; Chu, Chengcai; Schläppi, Michael R
Abstract : Glycosyltransferase OsUGT90A1 helps to protect cellular membranes during chilling and salt stress by enhancing antioxidant enzyme activity to reduce ROS levels, and to balance the stress response with growth. Abstract: Due to its subtropical origins, rice ( Oryza sativa ) is sensitive to low-temperature stress. In this study, we identify LOC_Os04g24110, annotated to encode the UDP-glycosyltransferase enzyme UGT90A1, as a gene associated with the low-temperature seedling survivability (LTSS) quantitative trait locus qLTSS4-1 . Differences between haplotypes in the control region of OsUGT90A1 correlate with chilling tolerance phenotypes, and reflect differential expression between tolerant and sensitive accessions rather than differences in protein sequences. Expression of OsUGT90A1 is initially enhanced by low temperature, and its overexpression helps to maintain membrane integrity during cold stress and promotes leaf growth during stress recovery, which are correlated with reduced levels of reactive oxygen species due to increased activities of antioxidant enzymes. In addition, overexpression of OsUGT90A1 in Arabidopsis improves freezing survival and tolerance to salt stress, again correlated with enhanced activities of antioxidant enzymes. Overexpression of OsUGT90A1 in rice decreases root lengths in 3-week-old seedlings while gene-knockout increases the length, indicating that its differential expression may affect phytohormone activities. We conclude that higher OsUGT90A1 expression in chilling-tolerant accessions helps to maintain cell membrane integrity as an abiotic stress-tolerance mechanism that prepares plants for the resumption of growth and development during subsequent stress recovery.